Absorption Process for Mitigating Green Oil Formation in Petrochemical Plants - W. Mahmoud Shehata; A. H. A. Hady; F. K. Gad (Chemical and Biochemical Engineering Quarterly)
The reaction of hydrochloric acid with hydrocarbons in petrochemical plants produces a viscous hydrocarbon compound called green oil. This oil can cause corrosion problems in the internal parts of equipment. As an alternative to the adsorption process used to remove hydrochloric acid, a simulation model is presented to efficiently absorb hydrochloric acid from an off-gas stream from an industrial process. Five suggested or ganic solvents were used in addition to water. Operating conditions that could affect HCl removal were investigated and optimized for all proposed solvents. Furthermore, an eco nomic study was performed for all proposed solvents based on required utility and capital cost estimates. The results showed that glycolic acid followed by ethylene glycol ranked second and third after water among the proposed solvents in terms of highest solubility, lowest solvent flowrate, and lowest capital and utility costs. Design Expert software was used to statistically analyze the simulation results.